Performance evaluation of superconducting fault current limiters for power system protection - Yogesh Shivaji Pawar; Sandip Rahane; Amita Panchamrao Thakare; Dipalee M. Kate; Jyoti P. Rothe; Dinesh Suryakant Wankhede; Kirti Vaidya; Hema Kale; Rakesh G. Shriwastava; Rahul Mapari (Institute of Advanced Engineering and Science, 2026)
This paper presents a comprehensive assessment of the performance of superconducting fault current limiters (SFCLs), emphasizing their capability for rapid and effective mitigation of severe fault currents. With the increasing global demand for electrical power, the occurrence of system faults has become more frequent, resulting in high fault currents that generate significant mechanical and thermal stresses. These stresses can compromise the integrity of power system components, including transformers and associated equipment. Conventional methods of fault mitigation often lack adaptability and responsiveness to varying fault conditions. In contrast, the SFCL serves as an efficient stabilizing device, offering superior performance by rapidly limiting fault currents within the first cycle and thereby enhancing the transient stability of the power system. This study examines fault scenarios such as single line-to-ground (L-G), double line-to-ground (L-L-G), and three-phase-to-ground (L-L-L-G) faults, with particular focus on the role of SFCLs in reducing the operational burden on circuit breakers and improving overall system reliability. This study evaluates the performance of SFCL under multiple power system fault scenarios using simulation analysis. The results show that SFCL effectively limits fault current, enhances transient stability, and reduces mechanical and thermal stress on circuit breakers, improving overall grid reliability.